HİPERTANSİF HASTALARDA ORBİTAL DOPPLER ULTRASONOGRAFİ - KALENDER, SUNA BİBAL (Fırat Üniveristesi, 2003)
l.OZET Hipertansiyonun retrobulber vasküler yapılar üzerindeki hemodinamik etkileri, renkli Doppler göz ultrasonografısi (RDGU) ile değerlendirildi. 01.08.2001-01.02.2002 tarihleri arasında hipertansiyon süreleri 1-30 yıl (ortalama 5.4 ± 5.5 yıl ) olan, sistemik hipertansiyon (HT) nedeni ile göz kliniğinde göz dibi muayenesi yapılan, yaşları 16 ile 85 arasında değişen (ortalama 50.3 ± 15 ) 50 olgu ile yaşlan 23 ile 69 yaş arasında değişen (ortalama 44.7 ± 1 1) 30 normotansif kişi çalışmaya dahil edildi. Her iki grubun iki gözünde de (160 göz) oftalmik arter (OA), santral retinal arter (SRA), posterior silier arter (PSA), piksistolik, end diastolik, rezistif indeks (Rİ), pulsatilite indeksi (Pİ) değerleri ölçüldü. Kişiler supin pozisyonunda, göz kapaklan kapalı, jel sürülerek, 7.5 MHz' lik lineer transdüser ile Toshiba Sonolayer SSH 140A renkli Doppler cihazı ( Tokyo/ Japonya ) ile değerlendirildi. Pİ değerlerinin; sağ SRA'da hipertansif grupta ortalama 1.30 ± 0.26 kontrol grubunda ortalama 1.15 ± 0.14 ( p= 0.004 ), sol SRA da hipertansif grupta ortalama 1.32 ± 0.30, kontrol grubunda ortalama 1.1 1 ± 0.19(p=0.0001) olduğu, Rİ değerlerinin; sağ PSA' da hipertansif grupta ortalama 0.64 ± 0.09 kontrol grubunda ortalama 0.63 ± 0. 09(p=0.013),sol PSA da hipertansif grupta ortalama 0.68 ± 0.09 kontrol grubunda 0.63 ± 0.06 (p=0.003) olduğu ve istatistiksel olarak anlamlı artış gösterdiği saptandı. Ayrıca sağ OA pik sistolik hızı hipertansif grupta ortalama 35.2 ± 9.2 cm /sn, kontrol grubunda 28.5 ± 7.5 (p=0.002), end diastolik hız hipertansif grupda ortalama 10.5 ± 4 kontrol grubunda 8.7 ± 7

Hemodynamic effects of hypertension on retrobulbar vascular structures were evaluated by color Doppler orbital ultrasonography. Between August 2001 and February 2002, 50 persons ranging in age from 16 to 85 years (mean 50.3±15 years) who have had hypertension for 1 to 30 years (mean 5.4 ± 5.5 years) and were examined for their retina in ophthalmology clinics due to systemic hypertension and 30 normotensive persons ranging in age from 23 to 69 years (mean 44. 7± 1 1 years) were inculuded in the study. Peak systolic and end diastolic flow velocities, resistivity index, pulsatility index values of Ophtalmic artery, Central retinal artery, Posterior ciliary artery in two eyes of each person in both group (160 eyes) were measured. Color Doppler US examinations were performed with color Doppler scanner Sonolayer SSH 140 A (Toshiba, Tokyo, Japan) with a linear 7.5 - MHz transducer while persons were at supine position and their eyes were closed. We found that in right central retinal artery; pulsatility index values were mean 1.30 ± 0.26 in hypertensive group, mean 1.15 ± 0.14 (p=0.004 ) in control group, in left central retinal artery; pulsatility index values were mean 1.32 ± 0.30 in hypertensive group, mean 1.11 ± 0.19(p=0.0001) in control group, in right posterior ciliary artery; resistivity index values were mean 0.64 ± 0.09 in hypertensive group, 0.63 ± 0.09 (p=0.013) in control group; in left posterior ciliary artery resistivity index values were mean 0.68 ± 0.09 in hypertensive group, 0.63 ± 0.06 (p=0.003). According to these results, it was noted that bothpulsatility index and resistivity index values in these arteries showed statistically significant increase in hypertensive group compared to control group. It was also detected that in right ophthalmic artery; peak systolic flow velocity was mean 35.2 ± 9,2 cm /s in hypertensive group, mean 28.5 ± 7.5 cm /s (p=0.002 ) in control group, end diastolic flow velocity was mean 10.5 ± 4 cm /s in hypertensive group, mean 8.7 ± 2.7 cm /s (p=0.040 ) in control group and it was found that peak systolic and end diastolic velocities of right ophthalmic artery showed statistically significant increase in hypertensive group compared to control group. Other measured parameters were not statistically significant between groups. Hemodynamic changes in retrobulbar vascular structures caused by hypertension can be demonstrated by Color Doppler US which is a noninvasive method. Key words : Hypertension, Color Doppler US, Orbita, Resistivity index, Pulsatility index
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Radyoloji ve Nükleer Tıp; Radiology and Nuclear Medicine